Enrichment of Bacterioplankton Able to Utilize One-Carbon and Methylated Compounds in the Coastal Pacific Ocean - Dinasquet, Julie; Tiirola, Marja; Azam, Farooq (Frontiers in Marine Science, 2018)
Understanding the temporal variations and succession of bacterial communities involved in the turnover of one-carbon and methylated compounds is necessary to better predict bacterial impacts on the marine carbon cycle and air-sea carbon fluxes. The ability of the local bacterioplankton community to exploit one-carbon and methylated compounds as main source of bioavailable carbon during a productive and less productive period was assessed through enrichment experiments. Surface seawater was amended with methanol and trimethylamine-N-oxide (TMAO), and bacterial abundance, production, oxygen consumption, as well as methanol turnover and growth rates of putative methylotrophs were followed. Bacterial community structure and functional diversity was examined through amplicon sequencing of 16S rRNA and methanol dehydrogenase (mxaF) marker genes. 2-fold increase in oxygen consumption and bacterial growth rates, and up to 4-fold higher methanol assimilation were observed in the amended seawater samples. Capacity to drawdown the substrates was similar between both experiments. In less productive conditions, methanol enriched obligate methylotrophs, especially Methylophaga spp., accounted for ∼70% of bacterial cells analyzed by fluorescence in situ hybridization and 16S rRNA gene sequencing, while TMAO enriched taxa belonged to Oceanospirillales and putative β- and γ-Proteobacterial methylotrophs. In the experiment performed during the more productive period, bacterial communities were structurally resistant, suggesting that facultative organisms may have dominated the observed methylotrophic activity. Moreover, enrichment of distinct methylotrophic taxa but similar activity rates observed in response to different substrate additions suggests a functional redundancy of substrate specific marine methylotrophic populations. Marine bacterioplankton cycling of one-carbon and methylated compounds appears to depend on the system productivity, and hence may have predictable temporal impacts on air-sea fluxes of volatile organic compounds.